KERAJINAN BATIK KAYU KREBET - Dyah Yuni Kurniawati (Institut Seni Indonesia Surakarta, 2014)
The article of â€œKeberadaan Kerajinan Batik Kayu Krebetâ€ (the existence of Krebet wood batik craft) is theresult of a research to know the existence, various products, and the process of wood batik. The methodused is descriptive qualitative that describes a phenomena. The research uses historical approach while theresearch location is Krebet, Sendangsari village, Pajangan, Bantul Residence. The research problems include:1) how the history of wood batik in Krebet area, and 2) what the various forms of wood batik in Krebet area.The research is supposed to give a description and literature contribution concerning wood batik craft thatbecomes one of the batik arts developments in Indonesia. The result of research shows that the existence ofwood batik craft in Krebet area appears through the impressive history. Before the wood batik craft appears,there have been developing a leather and wood craft in Krebet that is mask and wayang klithik popularized byGunjiar, Kemiskidi and Anton. In 1990s, the wood batik craft in Krebet got the development in coloringtechnique that is batik technique on wood by Windarti. The craft development in Krebet is influenced byinternal as well as external factors among other things are the craftsmen and the agentsâ€™ will to support thecraft existence. The wood batik craft has a function as an aesthetic element, practical function, and as toys.The practical function can be changed into aesthetic element because of the aesthetical decorations inbatik.Keywords: craft, wood batik, Krebet